Incidental intrapancreatic accessory spleen on computed tomography: the value of a stepwise imaging approach - Thor, Sze Mun; Goai, Xin Yi; Atanasov, Georgi D. (International Surgery Journal, 2026)
Intrapancreatic accessory spleen (IPAS) is a rare benign congenital anomaly that commonly occurs in the pancreatic tail and may closely mimic hyper vascular pancreatic neoplasms, particularly non-functioning pancreatic neuroendocrine tumours, leading to unnecessary surgical resection if misdiagnosed. We report a 61-year-old man in whom an incidental pancreatic tail lesion was identified on trauma computed tomography (CT) imaging. The patient was asymptomatic with normal laboratory findings and negative tumour markers. Dedicated CT pancreatic protocol demonstrated enhancement identical to the spleen, and subsequent MRI confirmed splenic-equivalent signal characteristics across all sequences. Definitive diagnosis was established using technetium-99m heat-damaged red blood cell scintigraphy. A stepwise, multimodality imaging approach enabled confident non-invasive diagnosis and avoided unnecessary pancreatic surgery. Recognition of characteristic imaging features of IPAS is essential to ensure appropriate conservative management of incidental pancreatic lesions.